Corrosion Inhibiting Evaluation of β-Cyclodextrin Functionalized Acrylamide Copolymer for X70 Steel in Sulfuricsolution - Qian, Huijie; Ai, Zhijiu (Current Analytical Chemistry, 2016)
Background: The corrosion of oil pipeline and equipment could lead to serious and technological problems. As the superior characteristics of inhibitor such as lower dosage and effective, corrosion inhibitor is widely applied to various fields. The aims of this paper are to mainly investigate the corrosion inhibition efficiency of β-cyclodextrin functionalized acrylamide copolymer (HCMPAM) on X70 steel in 0.5 M H2SO4 solution under different HCMPAM concentrations and different temperatures. Methods: The inhibition efficiency of copolymer on X70 steel in 0.5 M H2SO4 solution utilizing polarization, electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The inhibition efficiency of β-cyclodextrin functionalized acrylamide copolymer increases with the increase of concentration and decreases with the increase of temperature, the inhibition efficiency of HCMPAM exhibited the maximum values (94.8%) at the highest concentration of 150 mg L-1 at 293 K. Conclusion: HCMPAM copolymer acts as a mixed-type inhibitor, the inhibition efficiency increases with the increase of concentration and decreases with the increase of temperature. The adsorption of HCMPAM on X70 steel is found to obey the Langmuir isotherm and governed by chemisorptions. The adsorption of HCMPAM on X70 steel in 0.5 M H2SO4 solution was an exothermic process. The SEM and EDS results reveal that X70 steel form a protective layer and prevent the attack of acid on X70 steel surface.
Keywords: electrochemistry